Effect of Core strengthening along with Conventional Physiotherapy on Spinal Dysfunction in post operative modified Radical Mastectomy patients - Gat, Rutuja Rajendra; Bhimarao Kanase, Suraj (Journal of Neonatal Surgery, 2025)
Background: Modified Radical Mastectomy is a prevalent surgical intervention for breast cancer, involving the removal of breast tissue and lymph nodes while preserving chest muscles. Subjects often experience post-operative complications, including spinal dysfunction, chronic pain, and reduced mobility. These complications can lead to significant functional restrictions and postural alterations. Exercises are key component of treatment, can mitigate these adverse effects by enhancing spinal stability, alleviating chronic pain, and improving functional capacity. There role in enhancing movement and minimising disability needs to be evaluated Method: A total of 100 participants were enrolled in this study and randomly assigned to one of two groups: Group A (experimental group) and Group B (control group). Participants in Group A received a comprehensive exercise program consisting of core strengthening exercises in addition to conventional exercises, while those in Group B received conventional exercises only. A range of outcome measures were assessed at pre-test and post-test, including: Numerical Pain Rating Scale ,Spinal Range of Motion, Spinal Manual Muscle Testing ,Functional Rating Index, Spinal Static and Dynamic Stability Test , Postural Assessment. Result: The results of this study demonstrated significant improvements. Specifically, Group A exhibited: Reduced pain intensity (2.87 ± 0.65 vs 3.10 ± 0.82), Improved Manual Muscle Testing scores (4.56 ± 1.05 vs 4.14 ± 1.03), Enhanced Functional Rating Index scores (38.6 ± 4.2 vs 51.4 ± 14.1), Significant improvements in spinal mobility and postural alignment were observed in Group A compared to Group B.Enhanced spinal static (35.6 ± 4.2 vs 26.3 ± 4.9) and dynamic (60.1 ± 7.2 vs 42.6 ± 7.5) stability test. Conclusion: The integration of core strengthening exercises into conventional therapy yields significant improvements in spinal function and quality of life following modified radical mastectomy.